A novel approach to the decellularization of porcine skin as a potential bioink component for tissue engineering applications - Banzon, Jean Andrea Nicola T. (Animo Repository, 2024)
Bioengineering is key to addressing issues in regenerative medicine, with 3D bioprinting using extracellular matrix (ECM) derived from decellularized skin at the forefront of various tissue engineering applications. However, the fabrication of effective and compatible materials for 3D bioprinting remains to be a significant challenge, with existing bioinks facing several limitations (i.e., poor mechanical properties, and inadequate biocompatibility and printability). Hence, the main objective of this study was to develop a novel protocol that would efficiently delipidize and decellularize porcine dermis by combining the use of 70% isopropanol and 0.1% sodium dodecyl sulfate (SDS) with sonication. The protocol also aimed to preserve the structural integrity of the ECM similar to its native state. The loss of cells, preservation of ECM fibers, and ECM architecture were the criteria initially used to evaluate the effectiveness of the protocol. Hematoxylin & Eosin (H&E) staining and a modified histological scoring were done for this purpose. Based on this scoring system, 240 W and 9 hr sonication time were found to be the most ideal decellularization conditions. Image] (NIH) software was also utilized to quantify cell removal. The native and the decellularized samples that obtained the highest average score from the criteria mentioned (240 W, 9 hr) were analyzed using scanning electron microscopy with Energy-Dispersive X-ray (SEM-EDX) and Attenuated Total Reflectance - Fourier transform infrared (ATR-FTIR) spectroscopy. The SEM-EDX images showed some degradation of the decellularized porcine skin. On the other hand, the results of ATR-FTIR spectroscopy showed that after decellularization, functional groups found in the native samples were retained, implying that the decellularized porcine skin's structural integrity was preserved. To date, this is the first report on a protocol integrating the use of isopropanol and SDS, coupled with sonication, for decellularizing porcine dermis.